Upcycled Denim Backpack - Science History Institute (2023)
A backpack constructed from light blue wash denim fabric. The bag is "upcycled" from denim pants picked from Gikomba, the largest second-hand market in Kenya. Includes a bright pink dust cover made from an upcycled pillowcase.
Keywords: Denim; Backpacks; Dress accessories; Upcycling (Waste, etc.); Textile waste--Recycling; Textile waste